New Labor Management Guidelines and Changes in Cesarean Delivery Patterns. Issue 5 (May 2018) - Rosenbloom, Joshua I.; Stout, Molly J.; Tuuli, Methodius G.; Woolfolk, Candice L.; López, Julia D.; Macones, George A.; Cahill, Alison G.
Abstract : (Abstracted from Am J Obstet Gynecol 2017;217:689.e1–689.e8) In 2010, the Consortium of Safe Labor published labor curves based on a cohort of pregnant women with normal neonatal outcomes. The American College of Obstetricians and Gynecologists (ACOG) and Society of Maternal-Fetal Medicine responded with clinical recommendations and the proposal that a decrease in cesarean delivery (CD) rate could be achieved by avoiding the diagnosis of arrest of dilation at less than 6 cm.